Designing a Socio-Economic Model of Book Publishing with an Emphasis on the Cultural Economy - Akbari, Mostafa; Mirzaei, Khalil; Radfar, Majid (Iranian Journal of Educational Sociology, 2022)
Purpose: The primary objective of this study is to design a socio-economic model of book publishing with an emphasis on the cultural economy. Methods and Materials: This study employs a grounded theory approach with an inductive movement trajectory. The research process begins with data from the field and literature, leading to conceptualization and determination of relationships between concepts. The statistical population includes all available documents and in-depth interviews with experts in the field of book publishing. The sample size is determined based on theoretical saturation and purposive sampling. Data collection methods include in-depth unstructured and semi-structured interviews, and document studies aimed at discovering and extracting concepts and their interrelationships. Qualitative and conceptual content analysis methods were used through open, axial, and selective coding. Findings: The study identifies several critical factors influencing the book publishing industry in Iran. Key factors include liquidity (5.71%), content production (16.32%), economic conditions (12.06%), social trends (15.19%), cultural trends (4.34%), media (4.34%), legal frameworks (1.93%), and support and infrastructure. Content production emerged as the most significant factor, highlighting the importance of aligning publishing strategies with audience preferences and socio-cultural trends. Economic conditions and social trends also play crucial roles, indicating the need for adaptive strategies in managing financial and social dynamics. Conclusion: This study provides a comprehensive socio-economic model of book publishing, emphasizing the cultural economy. The findings underscore the importance of financial management, content alignment with audience preferences, and responsive strategies to economic and social changes. The research offers valuable insights for policymakers, publishers, and stakeholders to enhance the sustainability and resilience of the book publishing industry.